Local Culture Through Hyperlocal Media Using New Media Platforms - Rocky Prasetyo Jati (Universitas Sebelas Maret, 2021)
Hyperlocal media is one of the channels to obtain information related to locality activities. Previous research mentions hyperlocal media as another way to deliver news when local media cannot face technological disruption. Hyperlocal media is a media technology innovation for community media. Hyperlocal offers various forms of media delivery media. The main characteristic of hyperlocal media is the similarity of content sources originating from a geographical area to serve audiences from various regions beyond geographical reach. The ability of digital media and online media increases the chances of developing hyperlocal media. In the hyperlocal context, community media is no longer referred to as a media product but transforms into a 'platform'. This paper aims to examine community media developed by the Cultural Community to preserve local culture. This paper will clarify what content is proposed by the Cultural Community in Klaten. The method used to explore the activities of community cultural and community media is a qualitative approach. More specifically, this article examines the role of the manager of the Cultural Community in optimizing the technology used in traditional media into hyperlocal media. This study is based on ethnographic research and in-depth interviews with literature studies. This study describes the activities of the Cultural Community that uses the principle of the value of local wisdom to decide on the development of hyperlocal media